2013
DOI: 10.1177/0020764012471924
|View full text |Cite
|
Sign up to set email alerts
|

Integrating community mental health within primary care in southern Malawi: A pilot educational intervention to enhance the role of health surveillance assistants

Abstract: The HSAs' focus on the psychosocial concerns of individuals' 'distress' and 'risk' prepared the way for a practical set of culturally sensitive and therapeutic interventions and offers a potential path towards increasing the capacity of primary care mental health provision that is responsive to local understandings and experiences of distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…The findings of this study add to the growing evidence for policy makers of the effectiveness of mental health training and supervision of primary care workers in improving knowledge, confidence and case detection in a resourceconstrained country. The results are consistent with other studies done in South Africa, Kenya and Malawi in which knowledge and/or confidence of primary health care workers have been found to improve significantly after a mental health training intervention [14,19,20]. The results are also consistent with another study in Malawi which found an increased number of diagnosed mental health cases after a training intervention [21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of this study add to the growing evidence for policy makers of the effectiveness of mental health training and supervision of primary care workers in improving knowledge, confidence and case detection in a resourceconstrained country. The results are consistent with other studies done in South Africa, Kenya and Malawi in which knowledge and/or confidence of primary health care workers have been found to improve significantly after a mental health training intervention [14,19,20]. The results are also consistent with another study in Malawi which found an increased number of diagnosed mental health cases after a training intervention [21].…”
Section: Discussionsupporting
confidence: 91%
“…Three self-administered questionnaires were used to collect information from participants. These were the Community Attitudes toward Mental Illness (CAMI) scale developed by Taylor and Dear [12], the WHO mhGAP pre-and-post knowledge test for mhGAP based training [13] and a confidence questionnaire [14].…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach would not only be based on identifi cation of potential mental disorders, but should remain truly community-based and empowering (Wright et al, 2014). Tangible and concrete support is often of critical importance in community mental health interventions.…”
Section: Engaging Communities To Be Partners In Psychosocial Intervenmentioning
confidence: 99%
“…In Africa, alternative explanations for mental distress, such as bewitchment, taboos and the belief that it runs in families, reduce the chances of access to mental health care (Bird et al, 2011;Wright, Common, Kauye, & Chiwandira, 2014). Moreover, attitudes about mental illness are strongly influenced by traditional beliefs (e.g., supernatural causes) and remedies.…”
mentioning
confidence: 99%